Ambient CO oxidation on in-situ generated Co3O4 spinel surfaces with random morphology - Dubey, Anjani; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (ChemistrySelect, 2017)
The influence of the Co3O4 morphology on its redox behavior and catalytic performance in the CO oxidation reaction is studied. Three different Co3O4 morphologies were synthesized by precipitation and hydrothermal methods. TEM and SEM observations clearly show the different obtained morphologies: rods, wires and a mixture of plates and cubes. The textural properties depend on the morphology and the redox ones on the particle size. XRD analysis reveals a spinel structure in all solids but a preferential exposition of the [110] plane is presented in the Co3O4 rods. This preferential exposition, along with its higher specific surface area provides the rods with more efficient oxygen storage capacity resulting in an excellent catalytic performance compared to the other two morphologies.